Application of the Mixing Cell Model to the quantification of groundwater – surface water interaction - Matthews, Amy Jane (University of the Free State, 2013)
English: The significance of a reliable groundwater resource assessment is of growing importance as water resources are stretched to accommodate the growing population. An essential component of a groundwater resource assessment is the quantification of surface water – groundwater interaction. The insufficient amount of data in South Africa and the apparent lack of accuracy of current estimates of the groundwater component of baseflow lead to the investigation of a new methodology. The applicability of the Mixing Cell Model (MCM) to quantify the groundwater contribution to baseflow is examined to determine whether the method would be of use in groundwater resource assessments. The MCM simultaneously solves water and solute mass balances to determine unknown inflows to a system, in this application the groundwater component of baseflow. The incorporation of water quality data into the estimation of the surface water – groundwater interaction increases the use of available data, and thus has the ability to decrease the uncertainty of the estimation process. The balance equations are equated to an error term which is used in the quadratic programming solution of minimizing the square error sums in order to determine the unknown inflows. The mixing cell model is applied to datasets from the surface water – groundwater interaction test site developed by the University of the Free State, in addition to data collected along the middle Modder River during a fieldwork survey. The MCM is subsequently applied to a set of quaternary catchments in the Limpopo Province for which there are available calibrated estimates of the groundwater component of baseflow for the Sami and Hughes models. The MCM is further applied to the quaternary catchment D73F, located in the semi-arid Northern Cape, to assess the applicability of the mathematically based MCM in terms of a flow system located within a regionally-defined zero groundwater baseflow zone. The MCM results for each study area are assessed in comparison to groundwater baseflow volumes determined by the Pitman, Sami and Hughes models. A chemical hydrograph separation method which also incorporates water quality data is additionally reported for the study areas to further validate the MCM. The results indicate that the mixing cell model can reliably estimate the groundwater component of baseflow to a river. This application of the mixing cell model could contribute to increase and evaluate the accuracy of current groundwater baseflow estimates in South Africa, which will in turn ensure the responsible and sustainable use of the countries water resources.

Afrikaans: Die noodsaaklikheid van die betroubare assessering van grondwaterhulpbronne is van toenemende belang aangesien hulpbronne gerek word om in die behoeftes van die groeiende bevolking te voorsien. ŉ Wesenlike komponent van die assessering van grondwaterhulpbronne is die kwantifisering van oppervlakwater-grondwater-interaksie. Die ontoereikende hoeveelheid data in Suid-Afrika en die skynbare gebrek aan akkuraatheid van huidige ramings van die grondwaterkomponent van basisvloei het tot die ondersoek van ŉ nuwe metodologie gelei. Die toepaslikheid van die Gemengde Selmodel (GSM) om die bydrae van grondwater tot basisvloei te kwantifiseer, is in hierdie studie ondersoek om te bepaal of die metode nuttig in toekomstige assessering van grondwaterhulpbron sal wees. Die GSM los water- en opgeloste massabalanse gelyktydig op om onbekende invloei in ŉ stelsel te bepaal, in hierdie geval die grondwaterkomponent van basisvloei. Die inkorporering van watergehaltedata in die raming van oppervlakwater-grondwater-interaksie gee geleentheid vir groter gebruik van beskikbare data en het dus die vermoë om die vertroue in die ramingsproses te versterk. Die balansvergelykings word gelykstel aan ŉ foutterm wat gebruik word in die oplossing van kwadratiese programmering waar die kwadrate van die foutsomme geminimaliseer word ten einde die onbekende invloei te bepaal. Die GSM is toegepas op datastelle van die oppervlakwater-grondwater-interaksietoetsterrein wat by die Universiteit van die Vrystaat ontwikkel is, tesame met data wat gedurende ŉ veldwerkopname langs die Middel-Modderrivier versamel is. Die GSM is gevolglik toegepas op kwarternêre opvangsgebiede in die Limpopo-provinsie waarvoor daar gekalibreerde ramings van die grondwaterkomponent van basisvloei vir die Sami- en Hughes-modelle beskikbaar is. Die GSM is verder toegepas op die kwarternêre opvangsgebied D73F, geleë in die semi-ariede Noord-Kaap, om die geskiktheid van die wiskundiggebaseerde GSM te assesseer ten opsigte van ŉ vloeistelsel wat binne ŉ streeksgedefinieerde nul-grondwater-basisvloei-sone geleë is. Die GSM-resultate vir elke studiegebied is geassesseer in vergelyking met grondwater-basisvloei-volumes soos bepaal deur die Pitman-, Sami- en Hughes-modelle. Vir die studiegebiede is daar ook verslag gelewer oor ŉ chemiese hidrograaf-skeidingsmetode, wat ook watergehaltedata inkorporeer, ten einde die GSM verder te bevestig. Die resultate dui dat die GSM op ŉ betroubare wyse die grondwaterkomponent van basisvloei van ŉ rivier kan raam. Hierdie toepassing van die GSM kan bydra tot die verbetering en evaluasie van die akkuraatheid van huidige grondwater-basisvloei-ramings in Suid-Afrika, wat op sy beurt die verantwoordelike en volhoubare gebruik van die land se waterhulpbronne sal verseker.
Keywords: Quantification; Groundwater resource assessment (GRAII); Groundwater baseflow; Mixing cell model; Surface water – groundwater interaction; Dissertation (M.Sc. (Institute for Groundwater Studies))--University of the Free State, 2013; Aquifers